2001
DOI: 10.1126/science.1058673
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence for Substantial Variations of Atmospheric Hydroxyl Radicals in the Past Two Decades

Abstract: The hydroxyl radical (OH) is the dominant oxidizing chemical in the atmosphere. It destroys most air pollutants and many gases involved in ozone depletion and the greenhouse effect. Global measurements of 1,1,1-trichloroethane (CH3CCl3, methyl chloroform) provide an accurate method for determining the global and hemispheric behavior of OH. Measurements show that CH3CCl3 levels rose steadily from 1978 to reach a maximum in 1992 and then decreased rapidly to levels in 2000 that were lower than the levels when me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
559
8
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 592 publications
(615 citation statements)
references
References 26 publications
47
559
8
1
Order By: Relevance
“…Although several studies have suggested large changes in OH abundances in the atmosphere over the past decades, the direction of the change is apparently unclear. Studies by Krol et al (6) show a significant global increase in OH, whereas those by Prinn et al (7) show a decline in OH levels after 1988. Recent studies in the upper troposphere also have reported discrepancies between model predictions and measured HO x (where HO X ϵ OH ϩ HO 2 ) concentrations that strongly depend on solar zenith angles (8)(9)(10)(11).…”
mentioning
confidence: 82%
“…Although several studies have suggested large changes in OH abundances in the atmosphere over the past decades, the direction of the change is apparently unclear. Studies by Krol et al (6) show a significant global increase in OH, whereas those by Prinn et al (7) show a decline in OH levels after 1988. Recent studies in the upper troposphere also have reported discrepancies between model predictions and measured HO x (where HO X ϵ OH ϩ HO 2 ) concentrations that strongly depend on solar zenith angles (8)(9)(10)(11).…”
mentioning
confidence: 82%
“…Montzka et al (2011) inferred small interannual OH variability and trends (typical OH changes from year to year of less than 3 %) and attributed previously estimated large year-to-year OH variations before 1998 (e.g. Bousquet et al, 2005;Prinn et al, 2001) to overly large sensitivity of OH concentrations inferred from methyl chloroform measurements to uncertainties in the latter's emissions. However, Prinn et al (2005) also showed lower post-1998 OH variability that they attributed to the lack of strong post-1998 El Niño events.…”
Section: Oh Oxidationmentioning
confidence: 99%
“…[123][124][125][126][127] Long-term changes in global OH concentrations, and therefore in the atmospheric residence times of many gases, are a matter of great interest but remain highly uncertain. 128,129 Recent field campaigns have studied pollutants in the remote troposphere, 130 -133 the outflow from East Asia, 134 -143 the Indian subcontinent, 143 and North America. 144 -148 Several regional-scale studies have been carried out in the United States 149 -153 and Europe 154 -157 that demonstrated the enormous pollutant potential of major cites and "megalopolis" regions, as well as the fact that significant quantities of gaseous pollutants and fine particles can be transported and detected over intercontinental scales.…”
Section: Global Pollutant Transportmentioning
confidence: 99%